A study of Standard Chartered Bank Malaysia Berhad financial performance between theory and practiced / Siti Yuhani Abdul Manap - Abdul Manap, Siti Yuhani (2010)
This study reveals on the important of towards having a good financial performance. From that, the analysis on the financial performance will be carried out. The reason is because the stability of one bank is depending on their financial performance and how they utilize it for the bank benefits. They can operate effectively and efficiently by having good financial performance. From the financial statement (balance sheet and income statement), the evaluation of the bank performance can be done. To analyze the bank that involve in this study, the basic tool of financial analysis will be used. The financial ratios and that is appropriate for a bank will calculated based on the information disclosed on the financial statement of the bank. The study identifies the financial strength on certain criteria. There are five types of common ratios will apply to calculate the financial statement. An analysis has been given on each of the selected ratios after been calculated. From the ratio, we will know the financial performance of the bank. Thus, the determination whether the bank doing well in managing their financial activities in the last 5 years can be made.